Network programming theory application to project portfolio formation - Burkova, Irina; Titarenko, Boris; Hasnaoui, Amir; Roman, Titarenko (Serbian Journal of Management, 2021)
The paper deals with an application of the network (dichotomous) programming method for solving multi-extremal problems and discrete optimization problems. The concept of a generalized dual problem is introduced and a theorem on its convexity is proved. Network programming method is used to build a business-forming project portfolio as well as an algorithm for solving completely dependent related projects is developed. Also, this method is used to solve the problem of building a business-supporting project portfolio for which the lower cost estimate is obtained. A computational experiment is carried out to evaluate the suggested algorithm, which showed that for large dimensions of the problem it is more effective than for solving the problem by linear programming methods.
Keywords: project; project portfolio; network programming; generalized dual problem